Short communication. Influence of phenological stage on the antioxidant activity of Thymus zygis s. l. essential oil - Blanco Salas, J.; Ruiz Téllez, T.; Vázquez Pardo, F. M.; Cases Capdevila, M. A.; Pérez-Alonso, M. J.; Gervasini Rodríguez, C. (Spanish Journal of Agricultural Research, 2012)
When a species has proven antioxidant capacity and possible commercial application it is important to know whether or not this activity varies with the phenological stage of the raw material commodity. The present work aims to assess this topic for the case of Thymus zygis s.l. We analyzed the yield and the chemical composition (gas chromatographymass spectrometry) of its essential oil in five wild populations from the Southwest of Iberian Peninsula at flowering and fruiting stage. We measured their TEAC (Trolox equivalent antioxidant activity) values. The main components were p-cymene (flowering: 33.6-16.2%; fruiting: 43.2-30.3%), γ-terpinene (flowering: 13.5-5.78%; fruiting: 4.67-1.96%) and thymol (flowering: 46.45-22.2%; fruiting: 54.24-13.9%); the latest, especially high (flowering: 46.45%; fruiting: 54.24%) in one of the populations, identified as Thymus zygis ssp. gracilis (Boiss.) R. Morales, which showed the highest antioxidant activity as well. In the set of samples TEAC oscillated between 16.12-30.52 mmol Trolox L-1 (flowering) and 10.96-40.24 mmol Trolox L-1 (fruiting). No significant differences between antioxidant activity of both stages were found, but yields were significantly higher at flowering time. These levels of antioxidant activity are close to those achieved as highly antioxidant food products, as coffee or wine. This species can be a good raw material for agribusiness use, specially the population of Thymus zygis ssp. gracilis.